The reality of The services provded by civil society Organizations for the development of rural women the difficulties faced "A field study of civil society Organizations in the Governorate in Latakia " - Yasin, Ahlam (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Research aims to observation of The services provded by civil society Organizations in the governorate of Latakia for the development of rural women condition and to improve the Educational cultural ,economic ,health, Educational, and social level,and the difficulties facing that Organizations the implementation of its programs ,plans and activities in order to achieve the comprehensive development of rural women,and to achieve the goal of study the researcher designed an iner view cards based on the goals of the syrian NGOs, and it has been confirmed validity and reliatity and then applied to the sampl (60)members the sample of research included five organizations governorate of latakia results of research have shown there were differences of statistical significant between the average scores of members according to difficulties that facing in implementation of plans, programs,and activities to serve rural woman a ccording to changes of organization,and research confirms that the civilsociety organization a chieve some services related to sensitize raval women and educate,rehabilitate and traine her in all the educational,cultural, social,economicand health fields,but not at the level that helps to develop all round and full development to the degree of her participation in the development process whichis pushed by the Syrian society for the development and modernization process because she is half of society and the fundamental basis subsequent generations builts on.